PERUBAHAN ORIENTASI SEKSUAL PADA KOMUNITAS LESBIAN (ANAK BELOK) - Fella Purwanty; Lisya Chairani (Jurnal Psikologi TALENTA, 2018)
This study aims to determine changes in sexual orientation in the lesbian community. This study uses qualitative research methods with a case study approach. The informants in this study were as many as 5 (five) lesbian communities who were the subject of research in accordance with the research objectives. The internal process that occurs within the individual who initially is a heterosexual experiences disappointment in establishing heterosexual relationships resulting in trauma to the opposite sex can encourage individuals to develop same-sex relationships that aim to meet the needs of love and comfort. If the desire is fulfilled by a lesbian partner, then it will be a reinforcement in the individual to survive in the same relationship. Whereas families who have conflicts over the role of fathers have resulted in a deeper embedded judgment of men. The environment is also an important role in the process of changing sexual orientation. If the individual playing environment is dominated by lesbian women, individuals can be trapped in similar relationships. Community supervision is an important factor. If public supervision is weak, then individuals will remain lesbian. Whereas if the supervision of the community is strong, it will affect the individual to return to being heterosexual.